5,5 + \(\dfrac{3}{4}\) - 5 + \(\dfrac{1}{4}\)
(5,5 - 5) + (\(\dfrac{3}{4}\) + \(\dfrac{1}{4}\))
= 0,5 + 1
= 1,5
\(\dfrac{5}{2}\) x \(\dfrac{2}{3}\) + \(\dfrac{1}{4}\) : \(\dfrac{3}{2}\)
= \(\dfrac{5}{2}\) x \(\dfrac{2}{3}\) + \(\dfrac{1}{4}\) x \(\dfrac{2}{3}\)
= (\(\dfrac{5}{2}\) + \(\dfrac{1}{4}\)) x \(\dfrac{2}{3}\)
= (\(\dfrac{10}{4}\) + \(\dfrac{1}{4}\)) x \(\dfrac{2}{3}\)
= \(\dfrac{11}{4}\) x \(\dfrac{2}{3}\)
= \(\dfrac{11}{6}\)
Tính \(x\):
435 - [\(x\) + 16] = 425 : 17
435 - [\(x\) + 16] = 25
[\(x\) + 16] = 435 - 25
\(x\) + 16 = 410
\(x\) = 410 - 16
\(x\) = 394
\(x\) x \(\dfrac{1}{4}\) - \(\dfrac{3}{4}\) = 6 : \(\dfrac{3}{4}\)
\(x\) \(\times\) \(\dfrac{1}{4}\) - \(\dfrac{3}{4}\) = 6 x \(\dfrac{4}{3}\)
\(x\) x \(\dfrac{1}{4}\) - \(\dfrac{3}{4}\) = 8
\(x\) x \(\dfrac{1}{4}\) = 8 + \(\dfrac{3}{4}\)
\(x\) x \(\dfrac{1}{4}\) = \(\dfrac{32}{4}\) + \(\dfrac{3}{4}\)
\(x\) x \(\dfrac{1}{4}\) = \(\dfrac{35}{4}\)
\(x\) = \(\dfrac{35}{4}\) : \(\dfrac{1}{4}\)
\(x\) = \(\dfrac{35}{4}\) x 4
\(x\) = 35
\(x\) + 2\(\dfrac{3}{4}\) = 5\(\dfrac{2}{3}\)
\(x\) + \(\dfrac{11}{4}\) = \(\dfrac{17}{3}\)
\(x\) = \(\dfrac{17}{3}\)
\(x\) = \(\dfrac{17}{3}\) - \(\dfrac{11}{4}\)
\(x\) = \(\dfrac{68}{12}\) - \(\dfrac{33}{12}\)
\(x\) = \(\dfrac{35}{12}\)